2023
DOI: 10.1002/med.21985
|View full text |Cite
|
Sign up to set email alerts
|

The entrancing role of dietary polyphenols against the most frequent aging‐associated diseases

Abstract: Aging, a fundamental physiological process influenced by innumerable biological and genetic pathways, is an important driving factor for several aging‐associated disorders like diabetes mellitus, osteoporosis, cancer, and neurodegenerative diseases including Alzheimer's and Parkinson's diseases. In the modern era, the several mechanisms associated with aging have been deeply studied. Treatment and therapeutics for age‐related diseases have also made considerable advances; however, for the effective and long‐la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 281 publications
0
3
0
Order By: Relevance
“…A large number of previous studies have explored the application and molecular mechanism of quercetin and kaempferol as monomer drugs in the treatment of OP [ [20] , [21] , [22] , [23] ]. TCM emphasizes the compatibility of various herbs, and different DAIs play different roles in disease treatment.…”
Section: Resultsmentioning
confidence: 99%
“…A large number of previous studies have explored the application and molecular mechanism of quercetin and kaempferol as monomer drugs in the treatment of OP [ [20] , [21] , [22] , [23] ]. TCM emphasizes the compatibility of various herbs, and different DAIs play different roles in disease treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Nutrition is assumed to have an influence over the epigenetic mechanisms, which are effective in the pathogenesis of age-related diseases [ 29 ]. Dietary polyphenols have been recognized as efficient agents against aging and aging-related disorders [ 30 ]. A diet rich in vegetables and fruits has been found to prevent many diseases and to prolong lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…A diet rich in vegetables and fruits has been found to prevent many diseases and to prolong lifespan. It has also been demonstrated that the beneficial effect on longevity is due to a high content of polyphenols in the diet, indicating a direct relationship between polyphenol consumption and increased lifespan [ 30 ]. Recent findings indicate that phytochemicals like quercetin, resveratrol, curcumin, and fisetin regulate the activity of sirtuins [ 31 ] [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…10 Therefore, the consumption of polyphenol-rich foods has been shown to reduce the incidence of metabolic disorders, obesity, and T2D. 11 However, certain dietary polyphenols remain in the intestine for extended periods, allowing them to exert their beneficial effects by influencing the composition of the gut microbiota. 12 Increasing evidence from both human and animal studies indicates that specific polyphenols can alter the composition of the gut microbial community.…”
Section: Introductionmentioning
confidence: 99%